2017
DOI: 10.4995/wrs.2017.4533
|View full text |Cite
|
Sign up to set email alerts
|

Effect of competitive exclusion in rabbits using an autochthonous probiotic

Abstract: Animal nutrition has been severely challenged by the ban on antimicrobials as growth promoters. This has fostered the study of alternative methods to avoid colonisation by pathogenic bacteria as well as to improve the growth of animals and feed conversion efficiency. These new options should not alter the normal intestinal microbiota, or affect it as little as possible. The use of probiotics, which are live microorganisms that beneficially affect the host by improving its intestinal microbial balance, can be s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Similarly to our results, Lauková et al [ 21 ] and Szabóová et al [ 35 ] also reported higher ADWG through bacteriocinogenic and probiotic E. faecium AL41 (CCM8558) and CCM4231 strains application in rabbits. Improved body weight in rabbits was also noted after probiotics administration by Bovera et al [ 30 ], Bhatt et al [ 32 ] and Kalma et al [ 51 ]. On the other hand, after PPB CCM7420 addition increased the body weight only slightly (by 2.2%, Table 2 ), but in this group, better FCR was achieved, compared to strain application.…”
Section: Application Effects Of E Faecium Ccm7mentioning
confidence: 66%
See 2 more Smart Citations
“…Similarly to our results, Lauková et al [ 21 ] and Szabóová et al [ 35 ] also reported higher ADWG through bacteriocinogenic and probiotic E. faecium AL41 (CCM8558) and CCM4231 strains application in rabbits. Improved body weight in rabbits was also noted after probiotics administration by Bovera et al [ 30 ], Bhatt et al [ 32 ] and Kalma et al [ 51 ]. On the other hand, after PPB CCM7420 addition increased the body weight only slightly (by 2.2%, Table 2 ), but in this group, better FCR was achieved, compared to strain application.…”
Section: Application Effects Of E Faecium Ccm7mentioning
confidence: 66%
“…The feed conversion ratio (FCR) was influenced only through the Ent7420 administration and the combinative application of the CCM7420 strain with Eleutherococcus senticosus extract. The effect of probiotics, including registered probiotic preparations and new beneficial microorganisms on the growth performance of rabbits have been already described/reviewed; they usually confirmed the increased body weight [ 14 , 15 , 17 , 19 , 24 , 25 , 31 , 32 ]. The most of these studies described faster growth and higher weight gain of rabbits using probiotic preparations and feed additives based on the following bacterial strains and yeasts alone or in their combinations: Saccharomyces cerevisiae , S. boulardii , Bacillus licheniformis , B. cereus , B. cereus var.…”
Section: Application Effects Of E Faecium Ccm7mentioning
confidence: 99%
See 1 more Smart Citation
“…To achieve better production in rabbit husbandries, one possible way is the use of natural compounds, such as probiotics, prebiotics, synbiotics, bacteriocins, organic and fatty acids, and plant extracts, which can improve the health status of animals [1][2][3][4]. There are many reviews presenting their beneficial effects, mostly of probiotic applications to rabbits, with emphasis on reduction of pathogens and parasites in the gastrointestinal tract (GIT), stimulation of immunity, better growth performance, metabolism and nutrient utilization, and improved meat quality [5][6][7]. Application of natural antimicrobials, including probiotics, bacteriocins, and herbal extracts, can modulate and balance the intestinal microbiota instead of beneficial lactic acid bacteria, and enhance the immune response.…”
Section: Introductionmentioning
confidence: 99%
“…Because research into new antibiotics was scarce in European Union and United States (Wittebole et al, 2014), widespread appeals for alternatives to antibiotics have been voiced (Cunha et al, 2017).…”
Section: Introductionmentioning
confidence: 99%